Worse than war : Genocide, eliminationism, and the ongoing assault on humanity - Goldhagen, Daniel Jonah (New York : PublicAffairs, 2009)
A paradigm-changing investigation into the phenomenon of genocide and mass killing--explaining why genocides begin, are sustained, and end; why societies support them and why they happen so frequently; and how the international community should and can successfully stop them.
The choice ; Clarifying the issues. Eliminationism, not genocide ; Worse than war : our age of suffering ; Explaining eliminationist assaults. Why they begin ; How they are implemented ; Why the perpetrators act ; Why they end ; Modern eliminationist politics. Sources and patterns ; Thinking and acting ; Actual minds, actual words ; Changing the future. Prologue to the future ; What we can do.
Includes bibliographical references (p. 599-628) and index.
Keywords: Genocide -- Psychological aspects; Genocide -- Prevention; Racism -- Psychological aspects; Prejudices -- Psychological aspects; Hate -- Case studies; Group identity -- Case studies